Psychoeducation on Early Marriage to Increase Knowledge Among Adolescents of the Youth Community PPA Ester Bergema Nunbaun Sabu Sub-District Alak Village - Kinanggi, Ratnasari; Ananta, Aliffia (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research was motivated by the observation of adolescents who entered into early marriage by one of the members of the Youth PPA Ester community, echoing the background of compulsion. This research aims to increase knowledge related to early marriage, from the causes and the impact of its prevention. And can help in preventive action against early marriage among the PPA Youth Ester Bergema community in Nunbaun Sabu Village. With the expected target through psychoeducation about early marriage, it is hoped that it can increase the knowledge of adolescents who are members of the PPA Youth Ester Community echoing in Nunbaunabu Village related to early marriage. The subjects of this study were 54 members of the Ester Bergema Youth PPA community. The data collection technique in this study is to use a self-marriage scale to know how far the understanding of adolescent community members regarding self-marriage before and after being given psychoeducation. The results of the study are based on the implementation of psychoeducational interventions regarding early marriage that have been carried out to adolescent community members in Nunbaun Sabu Village; there is an increase in knowledge about early marriage. The implementation of psychoeducation activities can be carried out well with the enthusiasm of the teenagers and the assistance of the KelurahanNunbaun Sabu management